Langerhans’ cell histiocytosis: difficulty in establishing diagnosis (a case report) - Annie Kusumadewi; Landia Setiawati; Bambang Permono (Indonesian Pediatric Society, 2008)
A case of Langerhans’ cell histiocytosisthat previously diagnosed as tuberculous osteomyelitis,focusing on difficulty in diagnosis.